Comparative cellular pharmacokinetics and pharmacodynamics of siRNA delivery by SPANosomes and by cationic liposomes - Zhou, Chenguang (2012)
Mechanistic understanding of intracellular trafficking is important for the development of small interfering RNA (siRNA) delivery vehicles. Here, we describe a novel methodology to quantitatively analyze nanocarrier-mediated disposition of siRNA. Cellular uptake and cytoplasmic release of siRNA over time were quantified by measuring the fluorescence intensities of fluorescently-labeled siRNAs and molecular beacons using flow cytometry. This method was used to investigate the cellular pharmacokinetics (PK) of siRNA delivery by SPANosomes (SP) and by cationic liposomes (CL). The results showed that the superior pharmacodynamic (PD) response of SP was because it enhanced transport of siRNA into the cytoplasm compared to the CL. The divergent cellular pharmacokinetic profiles of the two formulations were associated with different cellular entry pathways. These findings can facilitate the rational design of more efficient siRNA delivery vehicles in the future.